Deteksi Molekuler Gen Penyandi Protein Virb11 pada Brucella abortus Isolat Lokal Asal Pinrang, NTT dan Strain Vaksin - Maze, Maria Gladis Bupu; Handijatno, Didik; Tyasningsih, Wiwik; Suwarno, Suwarno; Estoepangestie, Agnes Theresia Soelih; Ernawati, Rahaju (Jurnal Veteriner; Vol 21 No 4 (2020)DO - 10.19087/jveteriner.2020.21.4.503, 2020)
Brucellosis in cattle is a disease caused by Brucella abortus due to the reduction in livestock population caused by abortion, stillbirth, weak birth, infertility and sterility. Brucella abortus has several potential virulence factors, i.e. virB11 gene that encodes VirB11 protein is an important virulence factor acts as an ATPase for assembling organelles when the bacteria replicate, helping to complete the bacterial cycle and agress to another cells. The aim of this study are to re-identification Brucella abortus and detect virB11  gene as encoding of B. abortus VirB11 protein in local isolates from Pinrang, NTT, strain vaccines S19 and RB51. The isolates Brucella abortus were re-cultured in Brucella agar base and re-identification is followed by microscopic with Gram staining and biochemical tested with urease, citrat, indol and TSIA test.  virB11 gene was detected with PCR method. The PCR result showed virB11 gene have DNA band 720 bp. virB11 gene are present in local isolates from Pinrang, NTT, strain vaccines S19 and RB51.